2020
DOI: 10.3390/agronomy10121844
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Soil Health through Residue Management and Conservation Tillage in Rice-Wheat Cropping System of Punjab, Pakistan

Abstract: In South Asia, soil health degradation is affecting the sustainability of the rice-wheat cropping system (RWCS). Indeed, for the sustainability of the soil quality, new adaptive technologies, i.e., conservation tillage and straw management resource conservation, are promising options. This investigation was focused on the interaction of tillage and straw management practices and their effects on Aridisols, Yermosols soil quality, and nutrients dynamics with different soil profiles within RWCS. The long-term fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 73 publications
(86 reference statements)
2
9
0
Order By: Relevance
“…Previous studies have shown that conservation tillage has increased soil bulk density and pH compared with traditional tillage in South Asia rice and wheat planting system 30 . Another study showed that NT helped to increase soil bulk density in soybean fields in central India, and different tillage management could significantly affect soil physical properties 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that conservation tillage has increased soil bulk density and pH compared with traditional tillage in South Asia rice and wheat planting system 30 . Another study showed that NT helped to increase soil bulk density in soybean fields in central India, and different tillage management could significantly affect soil physical properties 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Crop management stabilizes the physiological process and metabolic pathways through mulches, extra irrigation, inorganic fertilizers, early sowing, exogenous application of micronutrient, osmoprotectants, and bioregulators. Integrating crop management practices with molecular genetics tools can ameliorate the adverse effects of high temperature, but need to further explore the strategies associated with high yield under heat stress [ 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 ]. The tolerance development can be achieved through a selection based on thermotolerant traits from existing germplasm and breeding utilizing land races and their wild relatives.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The nurseries of 28 genotypes were sown. For the healthy seedlings, recommended management practices were done ( Zahid et al, 2020 ). Earthen pots (12-inch diameter, 14-inch heigh) were filled with homogenized 12 kg soil (textured loamy, non-sterilized, EC 3.1 mS cm –1 , and pH 6.45).…”
Section: Methodsmentioning
confidence: 99%